Predictive Value of Eosinophilia and Basophilia in the Diagnosis of Bronchopulmonary Dysplasia in Premature Infants - Melek Buyukeren; Hasan Tolga Celik; Sule Yigit; Murat Yurdakok (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To compare the presence of eosinophilia and basophilia between two groups with and without bronchopulmonary dysplasia in preterm infants and, to investigate whether there was a correlation between the bronchopulmonary dysplasia severity and degree of eosinophilia.